If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.2x + -0.5x + -11 = 1 Reorder the terms: -11 + 0.2x + -0.5x = 1 Combine like terms: 0.2x + -0.5x = -0.3x -11 + -0.3x = 1 Solving -11 + -0.3x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + -0.3x = 1 + 11 Combine like terms: -11 + 11 = 0 0 + -0.3x = 1 + 11 -0.3x = 1 + 11 Combine like terms: 1 + 11 = 12 -0.3x = 12 Divide each side by '-0.3'. x = -40 Simplifying x = -40
| 5x+3(-5+5x)=1-x | | m/8=400/20 | | -9(x-3)=-12 | | -2x^2-4x=5 | | (x^2+6x+2)-(x^2+2x-8)=-2 | | -n+1=n-1 | | 4(a+8)-16=2(a+8)+2a | | -5(3-5r)+1=40-2r | | 13+15w=3w-w+4w | | 12m^2-3n^2= | | 172+2x+26=146+2x | | 4(2t+9)+7y=-24 | | 8x-4=4x+36 | | 16-4=4-4*4 | | t/12=324/18 | | -7x+6=126+3x | | x=1+5x | | 60=30+4y | | -21.944-3.7n=-4.4(0.9n+4.81) | | 3x+6=4-7x | | 3x(-4)+(96)-(-9)= | | 4-6x=x+4 | | 3(23)=5+8x | | 2(3d+10)=40 | | 8-(4-x)=5(1+x) | | 2(4+5x)=10(x+2)-12 | | -6x^2-5=0 | | 2[y-1]-6=0 | | -4(3h+10)=68 | | 10w+30+2=-10w+39 | | 4(3n+6)+2(-6n-2)=14 | | -16-2j=-34 |